Effects of β-carotene on glucose metabolism dysfunction in humans and type 2 diabetic rats - Jianjun Wu; Yinan Zhou; Hanqing Hu; Dawei Yang; Fan Yang (Compuscript Ltd, 2022)
Background Type 2 diabetes mellitus (T2DM) is a common chronic disease that is strongly associated with cardiovascular risk. Long-term high blood glucose levels may induce cardiomyocyte apoptosis, cardiac dysfunction and suppress fetal cardiomyocyte proliferation. Recent epidemiological studies have shown a link between antioxidant carotenoids and T2DM, but a comprehensive longitudinal study of this association has not yet been conducted. Methods We included participants with biological measurements for both serum cis-β-carotene and fasting glucose from NHANES (2001-2006). We divided the participants into quartiles according to serum cis-β-carotene levels and determined the association between these levels and glucose metabolism by using multivariable regression models adjusted for confounding factors. The mechanism through which β-carotene levels regulate plasma glucose levels was further investigated in vivo and in vitro. In addition, we performed a preliminary exploration of the effects of β-carotene on diabetic rats and primary cardiomyocytes. Results Higher cis-β-carotene (quartile 4) was associated with higher LDL-cholesterol levels but lower fasting blood glucose levels. However, T2DM rats subjected to β-carotene treatment showed diminished total triglycerides and LDL-cholesterol, and their β-carotene levels were associated with better cardiac function than that in the T2DM group (P<0.05). Moreover, β-carotene was found to be an important protective factor improving cardiac and mitochondrial function in diabetes. At non-cytotoxic doses, β-carotene clearly improved glucose uptake in insulin-resistant cells. Treatment with β-carotene increased GLUT4 and p-Akt expression, and attenuated the phosphorylation of IRS-1. Our data demonstrated that β-carotene improved cardiac mitochondria biogenesis in diabetes due to activation of PGC-1β. Conclusion Our results indicate that β-carotene can be used to treat metabolic disorders through inhibition of the insulin-resistance pathway in diabetes.